Financial modeling applications and data envelopment applications - Lawrence, Kenneth D.; Kleinman, Gary (Emerald, 2009)
Applications of Management Science is a blind refereed serial publication published on an annual basis. The objective of this research annual is to present state-of-the-art studies in the application of management science to the solution of significant managerial decision-making problems. It significantly aids the dissemination of actual applications of management science in both the public and private sectors. Volume 13 is directed toward the application of management science to financial management, specifically in portfolio analysis and in productivity management such as Data Envelopment Analysis (DEA). Arranged in two sections, the first comprises a collection of financial applications papers, while the second focuses on the use of DEA in such wide-ranging environments as airport operations, freight railroads, gynaecological departments, severe coastal storms, and performance evaluation and classification of universities and public schools. This volume will prove valuable to researchers and practitioners of management science and operations research, as well as being a vital companion to portfolio analysts and industrial and financial engineers alike.
Keywords: Business & Economics -- Decision-Making & Problem Solving.; Management decision making.; Budgeting & financial management.; Finance -- Mathematical models.; Data envelopment analysis.; elektronické knihy; electronic books